Non-denitrifying nitrous oxide-reducing bacteria - An effective N2O sink in soil. (December 2016) - Domeignoz-Horta, L.A.; Putz, M.; Spor, A.; Bru, D.; Breuil, M.C.; Hallin, S.; Philippot, L.
Abstract: Nitrous oxide (N2 O) is an important greenhouse gas and fundamental questions about the capacity of soil microbial communities to act not only as sources, but also as sinks for N2 O remains unanswered. We evaluated the capacity of non-denitrifying N2 O-reducers to mitigate the production of this greenhouse gas in soil. We showed experimentally that the addition of the non-denitrifying strain Dyadobacter fermentans, which possesses the previously unaccounted N2 O reductase NosZII, to 11 different soils significantly reduced N2 O production of up to 189% in more than 1/3 of the soils. The magnitude of this effect was significantly influenced by the soil pH and C/N ratio. Overall, our results provide unambiguous evidence that the overlooked non-denitrifying NosZII-type bacteria can contribute to N2 O consumption in soil. Highlights: Addition of the nosZ II strain D. fermentans can decrease soil N2 O production. D. fermentans' capacity to reduce N2 O is affected by low pH and C/N ratio. First evidence that non-denitrifying N2 O-reducers contribute to soil N2 O reduction.